Getting started with Python : understand key data structures and use Python in object-oriented programming - Romano, Fabrizio; Baka, Benjamin; Philips, Dusty (Learning path., 2019)
This Learning Path is a thorough and practical introduction to Python. You will learn all about Python data structures, its most common algorithms, and its objects, and use all these to create clever applications that will transform your business.